THE EFFICACY OF AQUEOUS AND METHANOL EXTRACTS OF Detarium microcarpum AGAINST MIGRATION OF Ostertagia ostertagi AND Trichostrongylus colubriformis - GAGMAN1, HALADU ALI; AHMAD, HAMDAN; IZZAUDIN NIK HIM, NIK AHMAD IRWAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The use of synthetic drugs to control gastrointestinal parasite of ruminant animals has resulted to several complications which call for exploring the use of plant material as an alternative anthelmintics. This research compared the sensitivity of O. Ostertagia and T. colubriformis, against methanol and aqueous extracts of D. Microcarpum using larval migration assay. The L3 larvae of O. Ostertagia and T. colubriformis were treated with aqueous and methanol extracts of D. microcarpum with the serial concentrations of 0.2, 0.4, 0.6, 0.8 1.0 and 2.0 mg/ml for two hours and were later transferred to migratory plates. Some of the larvae were treated with 0.02 μg/ml of ivermectin which served as positive control, whereas those treated with only M9 buffer solution served as negative control. Observation and counting of the migrated larvae were carried out after 24 hrs. Good larvicidal activity against the migration of both species was demonstrated by both the aqueous and methanol extract of D. microcarpum. Methanol extract demonstrated higher anthelmintic potential than aqueous extract against both larval species (P < 0.05). There was no significant diffrerence in the sensitivity between the two larval species to both the aqueous and the methanol extract as O. ostertagi recorded the IC50 values of 0.56 mg/ml and 0.351 mg/ml for aqueous and methanol extracts, whereas, T. colubriformis recorded0.59 mg/ml and 0.38 mg/ml aqueous and methanol extracts respectively. Even though ivermectin demonstrated a higher efficacy compared to the plant extracts (P < 0.05), D. microcarpum may serve as a source of lead compounds for the development of natural anthelmintic. There is need for isolation of active compounds in the extracts to be tested against the larvae, as well. There is need for the extracts to be tested in vivo.